The indexing policy in the practices of Brazilian institutional repositories: A diagnostic study from the perception of managers and indexers - Fujita, Mariângela Spotti Lopes [UNESP]; Tartarotti, Roberta Cristina Dal’Evedove; Dal’Evedove, Paula Regina; Panuto, Jéssica Cristina [UNESP] (SAGE Publications, 2023)
Institutional repositories aim to gather, treat and disseminate information resources produced in a given institution. The adoption of an indexing policy aims to improve information retrieval by the user community of the institutional repository, by proposing elements that standardize the practices of librarians who work in subject cataloging. The objective of the research is to analyze the perception of managers and indexers of Brazilian institutional repositories about the indexing policy for information organization and representation, with the specific objectives of performing a compared evaluation of elements and variables (characteristics, processes, and instruments) of the indexing policy regarding indexing and retrieval, discussion of vocabulary control procedures, and obtaining an overview focusing on the perception of the need for an indexing policy in Brazilian institutional repositories. Semi-structured interviews were applied to nine participants from eight institutional repositories to investigate the requirements, elements and variables of the indexing policy in the practice of managers and librarians of institutional repositories. The results reveal the need for improvements in the practices of the analyzed institutional repositories regarding the activities of subject cataloging, standardization of subject metadata, and vocabulary control, queries, and in carrying out tests or trials for continuous evaluation of indexing and information retrieval with users. The study also revealed that this scenario can be more positive if institutional repositories adopt an indexing policy for the practices they perform in repositories to be understood by managers and librarians as a tool to improve information retrieval. La política de indización en las prácticas de los repositorios institucionales brasileños: un estudio de diagnóstico desde la percepción de gestores e indexadores.
Keywords: Indexing policy; institutional repositories; librarian’s performance